Automotive industry application of aluminium-based hybrid metal matrix composite. (6th January 2020) - Ramesh, P.; Nataraj, M.
Monolithic materials cannot fulfil the demands for the advanced industrial requirements. Therefore, composite materials which possess the combined properties of different constituents are developed. In this experimental work, Al 6061 was used as matrix and Al2 O3, SiC and E glass short fibres were used as the reinforcement material. The composite specimen is fabricated through stir casting by varying the weight percentage of reinforcements and matrix materials. The investigation concluded that the load and sliding speed are expanded to improve the wear rate, and developing the sliding distance the wear rate is decreased. The different compositions of the materials are tested by using Pin on Disc apparatus to find the wear rate. From the experimental results the least wear rate is obtained in the composition (C4 ) of 70% wt of Al 6061, 15% wt of Al2 O3, 9% wt of SiC and 6% wt of E glass short fibre.